KETIDAKJELASAN LAFAZ DALAM KAIDAH TAFSIR (Analisis Aspek Khafi, Musykil, Mujmal, Mutasyabih) - Aprilita Hajar (LP2M Universitas PTIQ Jakarta, 2023)
It can be said that the rules of interpretation are guidelines compiled by scholars with in-depth study in order to obtain maximum results in understanding the meanings of the Qur'an, the laws, and various kinds of guidance contained therein. In this discussion, the author tries to explain with the aim of how to understand the utterance of nash. The discussions are detailed in such a way according to its importance in capturing the divine messages, especially the nash of the Qur'an, and it should be underlined that the rules of tafsir include many parts, one of which is the theory in the realm of Usul Fiqh science which is part of the Islamic branch of Science which broadly discusses how to explore and bring up the Shari'ah law from the nash in the Qur'an. The method used by researchers is a qualitative research method, which relies on the study of literature sourced from several books and journals. The result of this discussion is that learning the Arabic language is an urgency or an absolute requirement to draw meaning from the message of the Qur'an, because in studying the science of Usul Fiqh, in fact, it will never be separated from the Arabic language, in understanding the utterance in terms of its meaning, both clear and unclear. Pronouncements that can not be interpreted clearly or mubham, that's what causes a lot of differences in interpretation of the statement and it is important to be studied more deeply